Determinants of Adherence to Taking ARV (Anti Retro Viral) Drugs in PLWHA Patients at Simpang Kawat Public Health Center Jambi City in 2024 - Andika Aldi Putra; Hubaybah Hubaybah; Rumita Ena Sari (PT. Anagata Sembagi Education, 2024)
: Adherence to lifelong antiretroviral (ARV) therapy for people living with HIV/AIDS (PLHIV) is crucial to suppress the progression of HIV and prevent transmission to others. Data from the Jambi City Health Office show that out of 335 PLHIV referred to Simpang Kawat Public Health Center, only 222 individuals (66.2%) regularly adhere to ARV treatment. This study aims to identify the determinants of ARV adherence among PLHIV at Simpang Kawat Public Health Center, Jambi City, in 2024. The research was conducted from April to June 2024 with a sample of 63 individuals. Univariate and bivariate data analyses revealed significant relationships between ARV knowledge, family support, side effects, comorbidities, and the length of therapy with ARV adherence. However, age, gender, and education level were not significantly associated. These findings highlight the importance of more targeted education and social support approaches to improve PLHIV adherence. A holistic approach to addressing medication side effects and increasing family involvement will support the long-term success of the therapy.